Les politiciens maîtrisent-ils leur image ? - Thierry Giasson (Communication)
What image do politicians wish to project during a televised debate ? Do they manage to maintain this image throughout the debate ? The analysis answers these questions by studying the televised French-language debate during the 2000 federal electoral campaign. The results presented here are taken from interviews with political consultants who participated in preparing the leaders for the debate and from a content analysis of the non verbal components of the image projected by each leader during the course of the exchanges. The analysis allows for the exploration of Canadian political communication from a new angle by focussing on the problematic of the image management of politicians as they prepare for televised electoral debates.